Kidney Tubular Damage Secondary to Deferasirox: Systematic Literature Review - Martin Scoglio; Maria Domenica Cappellini; Emanuela D'Angelo; Mario G. Bianchetti; Sebastiano A. G. Lava; Carlo Agostoni; Gregorio P. Milani (MDPI AG, 2021)
Deferasirox is a first-line therapy for iron overload that can sometimes cause kidney damage. To better define the pattern of tubular damage, a systematic literature review was conducted on the United States National Library of Medicine, Excerpta Medica, and Web of Science databases. Twenty-three reports describing 57 individual cases could be included. The majority (n = 35) of the 57 patients were ≤18 years of age and affected by thalassemia (n = 46). Abnormal urinary findings were noted in 54, electrolyte or acid-base abnormalities in 46, and acute kidney injury in 9 patients. Latent tubular damage was diagnosed in 11 (19%), overt kidney tubular damage in 37 (65%), and an acute kidney injury in the remaining nine (16%) patients. Out of the 117 acid-base and electrolyte disorders reported in 48 patients, normal-gap metabolic acidosis and hypophosphatemia were the most frequent. Further abnormalities were, in decreasing order of frequency, hypokalemia, hypouricemia, hypocalcemia, and hyponatremia. Out of the 81 abnormal urinary findings, renal glucosuria was the most frequent, followed by tubular proteinuria, total proteinuria, and aminoaciduria. In conclusion, a proximal tubulopathy pattern may be observed on treatment with deferasirox. Since deferasirox-associated kidney damage is dose-dependent, physicians should prescribe the lowest efficacious dose.